Utilización de pulpa de café biofermentada como suplemento alimenticio en el engorde de toretes al pastoreo en el cantón Chaguarpamba provincia de Loja - Córdova Encalada, Max Leonardo (2014)
This research project was carried out in the Canton of Chaguarpamba, located in the central part of the province of Loja, a distance of 111.4 km from the city of Loja. The project was carried out in order to assess the productive and economic indicators of crossbred bulls, kept on grass pasture, supplemented with a ration of biofermentated coffee pulp and sugarcane. The trial lasted 90 days and used 15 crossbred steers, 18 months old with an average weight of 140 kg. Three experimental groups of five animals each were formed, which were provided with 10% and 15% supplementary rations of biofermentated coffee pulp, mixed with chopped sugar cane, the third group served as a control group. A randomized block design using three treatments and five repetitions was employed. The bio-fermentation process of coffee pulp was used over a 72 hour period, with the addition of 1.5% of urea; 0.5% of mineral salts and 10% sugar cane juice. After drying and grinding up this was then incorporated into the diet of the animals prior to an adjustment period of 15 days. The following variables were studied: Feed intake, weight gain, feed conversion and profitability. Statistical analysis was performed using the Duncan test. The results showed that the highest dry matter intake, daily gain, feed conversion and performance rate was achieved in treatment two with 5.04 kg DM / animal / day, 700.00 g / animal / day; a 7.5 feed conversion rate and a 23.3% performance rate.